2021
DOI: 10.3390/jof7030205
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Activity of Agricultural Fungicides against Clinical Aspergillus Isolates with and without Environmentally and Medically Induced Azole Resistance

Abstract: Azole resistance is an emerging problem in patients with aspergillosis. The role of fungicides for resistance development and occurrence is not fully elucidated. EUCAST reference MICs of 17 fungicides (11 azoles and 6 others), five azole fungicide metabolites and four medical triazoles were examined against two reference and 28 clinical isolates of A. fumigatus, A. flavus and A. terreus with (n = 12) and without (n = 16) resistance mutations. Eight/11 azole fungicides were active against wild-type A. fumigatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…The net yield responses from standard fungicide treatments in Northern-European countries are negative in 1 to 2 seasons out of 10 ( Jalli et al., 2020 ), which indicates that no fungicide treatments should have been carried out in those years. This highlights the necessity of introducing prediction schemes to support farmers’ decision-making ( Jørgensen et al., 2020b ).…”
Section: Azole Use In a Greater Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The net yield responses from standard fungicide treatments in Northern-European countries are negative in 1 to 2 seasons out of 10 ( Jalli et al., 2020 ), which indicates that no fungicide treatments should have been carried out in those years. This highlights the necessity of introducing prediction schemes to support farmers’ decision-making ( Jørgensen et al., 2020b ).…”
Section: Azole Use In a Greater Contextmentioning
confidence: 99%
“…An extensive Chinese survey has linked the prevalence of resistant A. fumigatus in agricultural fields to the applications of azole fungicides ( Cao et al., 2021 ). Specific studies showed variations in the different azoles’ selection potential as a result of variable sensitivity and affinity to the target gene in A. fumigatus ( Snelders et al., 2012 ; Jørgensen et al., 2021b ). Although a lot of research has been dedicated to this topic in recent years, the role of azole fungicides for resistance development and occurrence in A. fumigatus has not yet been fully elucidated ( Gisi, 2014 ; Barber et al., 2020 ; Fraaije et al., 2020 ).…”
Section: Azole Use In a Greater Contextmentioning
confidence: 99%
“…Azole fungicides, i.e., bromuconazole, difenoconazole, epoxiconazole, enilconazole, metconazole, prochloraz, propiconazole, prothioconazole-desthio, and tebuconazole, play an important role in the development of environment-derived azole-resistant Aspergillus isolates leading to cross resistance to medical azoles [169,172,173].…”
Section: Etiology and Clinical Significancementioning
confidence: 99%
“…Many triazoles and imidazoles are active against A. fumigatus [20,21], hence the introduction of medical triazole therapies to combat CPA and IA in the late 1980s [6,10]. Triazoles are currently the first-line choice of medical treatment for patients suffering from these conditions.…”
Section: Demethylation Inhibitor (Dmi) Antifungals In the Clinic And Fungicides In The Environmentmentioning
confidence: 99%
“…A number of DMI fungicides used in the outside environment are intrinsically active against A. fumigatus [20,21,56,57]. Cross-resistance in ARAf isolates to these DMIs and the different triazoles used in medicine is common, but not always the case, depending on the genetic configuration of the ARAf genotype [20,52,57].…”
Section: Resistance To Dmi Fungicides In a Fumigatusmentioning
confidence: 99%